Composite dynamics in Sp(2N) gauge theories - Ed Bennett (EPJ Web of Conferences, 2022)
Sp(2N) gauge theories with fermonic matter provide an ideal lab- oratory to build extensions of the standard model based on novel composite dynamics. Examples include composite Higgs along with top partial compos- iteness and composite dark matter. Without fermions, their study also comple- ments those based on SU(Nc) gauge theories with which they share a common sector in the large Nc = 2N limit. We report on our recent progress in the numerical studies of Sp(2N) gauge theories discretised on a four-dimensional Euclidean lattice. In particular, we present preliminary results for the low-lying mass spectra of mesons and chimera baryons in the theories with N = 2. We also compute the topological susceptibility for various values of N, extrapo- late the results to the large N limit, and discuss certain universal properties in Yang-Mills theories.